Comparative study of the removal of phenolic compounds by biological and non-biological adsorbents - Navarro A.E. (2009)
The authors thank the National Council of Science and Technology of Peru for the grant 152-2006-CONCYTEC-OAJ used in carrying out this work. We also wish to extend our grateful appreciation to Rosario Portales, Todd Kelly and Richard Buran for their contributions and critical comments regarding this research.